Ireland's income distribution in comparative perspective - Brian Nolan; Timothy Smeeding (Luxembourg Income Study (LIS), 2004)
One of the most frequently expressed concerns about the unprecedented economic boom that Ireland experienced in the second half of the 1990s has been that the benefits were not shared evenly, that rising living standards were accompanied by widening gaps leaving Ireland with a particularly unequal distribution of income. This paper examines Ireland's income distribution in comparative perspective, and seeks to shed some empirical light on what happened during the boom and how Ireland compares to other rich countries. It begins by using the data from the OECD and the Luxembourg Income Study to compare Ireland's degree of income inequality with other advanced countries. It then looks in some detail at what alternative sources of survey data suggest about key trends in income inequality in Ireland from 1994 to 2000. Since there is a particular interest in what happened right at the top of the distribution, this is then examined using data from the administration of the income tax system. We conclude that the spectacular economic growth in the past decade has seen the gap in average income between Ireland and the richer OECD countries narrow dramatically. However, this growth has not greatly affected the Irish ranking in terms of income inequality. Ireland remains something an outlier among rich European nations in its high degree of income inequality, though still falling well short of the level seen in the USA. In the end, Ireland's new-found prosperity provides a 'social dividend', and choices about how it is used will fundamentally affect whether the current high level of income inequality persists into the future.
Keywords: 330; Einkommensverteilung; Irland; USA; Schweden; Niederlande; Finnland; Kanada; Deutschland; Großbritannien; Belgien